Salvia deserti Decne., an endemic and rare subshrub from Arabian desert: antidiabetic and antihyperlipidemic effects of leaf hydroethanolic extracts - Guetat, Arbi; Selmi, Slimen; Abdelwahab, Abdelrhman T.; Abdelfattah, Marwa A.; Elhaj, Abd Ealrhman M.; Mogharbel, Roaa T.; Abualreish, M. J. A.; Alanazi, Abdullah F.; Hosni, Karim; Mejri, Naceur; Boulila, Abdennacer (Frontiers in Pharmacology, 2025)
IntroductionDiabetes is a major health issue that has reached alarming levels worldwide. Although their effectiveness, the antidiabetic drugs have many side effects such as cardiovascular diseases, kidney failure, and hepatic complications. Many plant species of the genus Salvia L. such as “Arabian desert sage” (Salvia deserti) should began to be the focus of phytochemical and bioactivity studies.MethodsThe study aims to investigate, first-ever, the antidiabetic and antihyperlipidemic effects of the leaf hydroethanolic extract of S. deserti, an endemic and rare subshrub from Arabian desert. A single intraperitoneal injection of alloxan monohydrate (160 mg/kg) was used to induce type-2 diabetes. Development of diabetes was confirmed by measuring the blood glucose collected from the tail vein after 72 h of alloxan injection. Oral administration of hydroethanolic extracts of S. deserti at 200 and 400 mg/kg for 14 days were tested on the alloxan-induced diabetic mice and animals were divided into 6 groups of 6 mice each. The identity of phenolic compounds of the hydroethanolic extract of S. deserti was conducted through HPLC-Electrospray Ionization-Mass Spectrometry (LC-ESI-MS) analyses.ResultsOral administration of hydroethanolic extract of S. deserti at 200 and 400 mg/kg for 14 days significantly decreased blood glucose and restored the hepatic and renal function by reducing the levels of ALT, AST, ALP, GGT, LDH, urea and creatinine. An improved lipid profile as revealed by the reduced levels of TC, TG and LDL coupled with increased level of HDL was also observed. Moreover, treatment with S. deserti hydroethanolic extract relieved oxidative stress (reduction of MDA and H2O2) and the activity of antioxidant enzymes SOD, CAT and GPx. The presence of several phenolic compounds (derivatives of ferulic, coumaric, and caffeic acids, among other derivatives) could at least in part explain the obtained data and empower the use of S. deserti as a source of bioactive ingredients with antioxidant, antidiabetic and antihyperlipidemic properties.DiscussionOur research has unveiled S. deserti as a source of potential to effectively manage diabetes and its associated dyslipidemia by improving antioxidant status, recovery of the liver and kidney functions and presumably by increasing insulin secretion and sensitivity of peripheral tissues to insulin.